2005
DOI: 10.1111/j.1774-9987.2005.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose and Plasminogen Activator Inhibitor‐1 on Collagen Metabolism in the Peritoneum

Abstract: Nonphysiological solutions containing high glucose levels have been considered an important factor in the etiology of fibrotic changes in long-term continuous ambulatory peritoneal dialysis (CAPD) patients. At the same time, increased Plasminogen Activator Inhibitor (PAI)-1 secretion has been reported to correlate with fibrotic changes. We suspected that the high glucose content of peritoneal dialysis solution may induce peritoneal sclerosis via up-regulation of PAI-1 gene expression. In this study, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
3
26
1
Order By: Relevance
“…Furthermore, the marked increase in CTGF levels by factors implicated in the development of peritoneal membrane fibrosis suggests its involvement in underlying pathophysiologic mechanisms [11,40] . Indeed, the expressions of collagen type 1 and 3 mRNA in RPMCs also increased directly with the addition of aldosterone, similarly to the expression in rat mesangial cells observed in recent reports [41,42] . Stimulation of CTGF synthesis is mediated via the TGF-␤ -specific Smad signaling pathway [43] .…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, the marked increase in CTGF levels by factors implicated in the development of peritoneal membrane fibrosis suggests its involvement in underlying pathophysiologic mechanisms [11,40] . Indeed, the expressions of collagen type 1 and 3 mRNA in RPMCs also increased directly with the addition of aldosterone, similarly to the expression in rat mesangial cells observed in recent reports [41,42] . Stimulation of CTGF synthesis is mediated via the TGF-␤ -specific Smad signaling pathway [43] .…”
Section: Discussionsupporting
confidence: 58%
“…It has been shown that glucose induces peritoneal fibrosis by stimulating PAI-1 expression [25] , which can be blocked by anti-TGF-␤ strategies [26] . It is also known that PAI-1 is a component of ECM and a target gene of TGF-␤ because several Smad-binding boxes (CAGA) are in the PAI-1 promoter [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts were isolated from rat peritoneum as described previously for modified differential subcultures [20,21] . Briefly, rat peritoneal fibroblasts (RPFs) were obtained from the peritoneal wall of male Wistar rats weighing about 150 g by a standard trypsin/ethylenediaminetetraacetic acid (EDTA) digestion method.…”
Section: Cell Culturementioning
confidence: 99%